Invited Perspective: Uncovering the Hidden Burden of Tropical Cyclones on Public Health Locally and Worldwide - Parks, Robbie M.; Guinto, Renzo R * (National Institute of Environmental Health Sciences, 2022)
As climate change and health researchers of Filipino heritage, we both are all too directly familiar with the cycles of devastation that typhoons (such as Typhoon Haiyan1 in 2013 and Typhoon Noru2 in 2022) and other tropical cyclones can leave in their path. For our families, the destruction wrought by tropical cyclones has manifested as downed trees, damaged or destroyed homes, and uprooted lives. Sadly, such traumatic experiences are commonplace when tropical cyclones make landfall, be it in the Philippines, China, Mexico, the United States, or elsewhere.